Assessment and Forecasting of the Parameters of the Business Climate of Russian Manufacturing Industries - Elena V. SIBIRSKAYA; Lyudmila V. OVESHNIKOVA; Irina Y. VLADYKO; Anna N. ZUEVA (Communications of International Proceedings, 2021)
The development of manufacturing industries in Russia faces a number of difficulties and problems, which include depreciation of fixed assets, relatively low competitiveness of domestic products on the world market, a small share in the export of manufacturing products, especially high-tech products, dependence on imported products on the domestic market, lack of working capital, deterioration of the business climate. The business climate at the beginning of 2021. It is determined by the problems associated with the consequences of the COVID-19 pandemic, which were caused by a drop in demand for products, the output of some types of manufacturing industries. The article presents the main results of the study of the business climate of manufacturing industries in the framework of strategic planning and suggests measures to change it, taking into account the Strategy for the Development of the manufacturing industry until 2024 and for the period up to 2035.
Keywords: Business Climate; Planning; Forecasting; Manufacturing; Scientific And Technical Development.